43.2k views
2 votes
2. Which equation has no solution? *

1 poir
O x-5(x + 4) = 2(2x + 7) + 6
O 5(x + 1) - 3x = 5 - 2(5 - x)
O 1 - 3(x + 3) = 2(3x – 4) - 9x
O 3(x - 4) + x = 4(3 - x)

User Zodman
by
4.7k points

1 Answer

2 votes

Answer:

5(x+1) - 3x = 5 - 2(5-x)

Explanation:

This has no solution. Explanation:

5(x+1) - 3x = 5 - 2(5-x)

5x + 5 - 3x = 5 -10 + 2x

2x + 5 = -5 + 2x

5 = -5

From the result above, clearly there is no x to satisfy the equation, because 5 (to the left) can never be the same as -5 (to the right).

User Hermeneck
by
4.7k points